2012
DOI: 10.3892/ol.2012.868
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of rectal carcinoid patients undergoing surgical resection

Abstract: Abstract. The aim of this study was to clarify the clinical aspects, histopathological features and prognosis of patients with rectal carcinoids, focusing on properties associated with metastasis, in order to gain insights into appropriate management. A total of 20 patients (15 males, 5 females; mean age, 54.9 years; range, 23-71) who underwent surgery for rectal carcinoid tumors at the Department of Colorectal Surgery, Hyogo College of Medicine, between May 2000 and January 2011 were analyzed. Ki-67 immunosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Many previous studies have reported the presence of lymphovascular invasion in rectal NETs as a strong risk factor for metastasis [9][10][11][12][13][14][15][16][17]. However, the fact that nearly a half of the small rectal NETs could be positive for lymphovascular invasion raises a question about the clinical significance of this histopathologic variable.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Many previous studies have reported the presence of lymphovascular invasion in rectal NETs as a strong risk factor for metastasis [9][10][11][12][13][14][15][16][17]. However, the fact that nearly a half of the small rectal NETs could be positive for lymphovascular invasion raises a question about the clinical significance of this histopathologic variable.…”
Section: Discussionmentioning
confidence: 97%
“…To date, in addition to tumor size and depth of invasion, several other risk factors for metastasis have also been reported, including the patient age, presence of lymphovascular invasion, tumor proliferative activity, presence of perineural invasion, and presence of atypical surface characteristics (depression and ulceration) [9][10][11][12][13][14][18][19][20][21][22]. Among these, lymphovascular invasion is the most wellestablished risk factor for metastasis of rectal NETs, and some studies suggest that the presence of lymphovascular invasion could be a risk factor for metastasis even in tumors smaller than 10 mm in size [9][10][11][12][13][14][15][16][17]20].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Historically, endoscopic resection has been considered curative in cases of rectal NETs ≤10 mm in size (1,15). However, several studies and case reports have reported metastasis of small rectal NETs (16)(17)(18)(19). We performed EUS for all 76 lesions before endoscopic resection.…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence of lymphovascular invasion and high Ki-67-ratio seem to be the most important risk factors 3. In this case, there is only one important risk factor, that is, high Ki-67-ratio.…”
Section: Discussionmentioning
confidence: 78%